Perancangan Sistem Informasi Kerja Sama STMIK AKI Berbasis Web dengan Pendekatan EAP - Krisnata Ariel Wahyudi; Listiarini Edy Sudiati; Eko Prasetyo (Jurnal Teknologi Terpadu, 2025)
Collaboration management in higher education is a strategic activity that supports the improvement of education, research, and community service. However, the existing system at STMIK AKI still faces several challenges, particularly in manual documentation, delays in monitoring contract validity, and limited transparency in reporting. This study aims to design a web-based collaboration information system using the Enterprise Architecture Planning (EAP) approach. The system blueprint was evaluated through expert judgment combined with a Focus Group Discussion (FGD) involving stakeholders from collaboration units, IT expert and institutional leaders. The results of this study produced a blueprint for a collaboration information system comprising modules for partner and document management, contract monitoring with automated notifications, and an executive dashboard for evaluating collaboration achievements. Validation through FGD confirmed that this system design is feasible to implement, with improvements to security aspects. The system is expected to increase document management efficiency, reduce delays in contract extensions, and support decision-making by providing more accurate, real-time data. This research contributes a practical system design that can serve as a reference for implementation and as a foundation for the development of integrated collaboration systems in higher education institutions.